2007
DOI: 10.1007/s11606-007-0240-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Primary Care Residents’ Performance in Brief Alcohol Intervention: A Randomized Controlled Trial

Abstract: BACKGROUND: Brief alcohol interventions (BAI) reduce alcohol use and related problems in primary care patients with hazardous drinking behavior. The effectiveness of teaching BAI on the performance of primary care residents has not been fully evaluated. METHODS:A cluster randomized controlled trial was conducted with 26 primary care residents who were randomized to either an 8-hour, interactive BAI training workshop (intervention) or a lipid management workshop (control). During the 6-month period after traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
11

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 36 publications
1
35
0
11
Order By: Relevance
“…Of even greater concern to the authors was that counselors left the workshop viewing themselves as fairly proficient in the approach and, therefore, perceived little need for further training (Miller & Mount, 2001). A more recent study found no difference between MI-trained and non-MItrained residents relating to clients' reported number of drinks consumed and mean number of drinks per week (Chossis et al, 2007). Conversely, an evaluation of a more comprehensive training process found significantly more change talk and less resistance in clients of MI-trained counselors who received follow-up coaching, an effect that was sustained at 4-month follow-up (Miller, Yahne, Moyers, Martinez, & Pirritano, 2004).…”
Section: What Is the Most Effective Methods Of Learning Mi?mentioning
confidence: 93%
“…Of even greater concern to the authors was that counselors left the workshop viewing themselves as fairly proficient in the approach and, therefore, perceived little need for further training (Miller & Mount, 2001). A more recent study found no difference between MI-trained and non-MItrained residents relating to clients' reported number of drinks consumed and mean number of drinks per week (Chossis et al, 2007). Conversely, an evaluation of a more comprehensive training process found significantly more change talk and less resistance in clients of MI-trained counselors who received follow-up coaching, an effect that was sustained at 4-month follow-up (Miller, Yahne, Moyers, Martinez, & Pirritano, 2004).…”
Section: What Is the Most Effective Methods Of Learning Mi?mentioning
confidence: 93%
“…Other successful interventions have increased the knowledge and skills of generalist residents, 26,32 but have not demonstrated the potential to shift the values and culture of a residency program to include more SU training. In addition to being pivotal educators in the clinical training of students and residents, CRs have additional strengths.…”
Section: Discussionmentioning
confidence: 99%
“…16,29,30 Substance use education aimed at improving physician trainees' attitudes and clinical practice has been effective. 31,32 Confidence in ability to screen and refer patients is positively associated with perceived responsibility and clinical practice. 33 Wider dissemination of these practices requires creative strategies to develop a workforce that is knowledgeable about stateof-the-art approaches to patient management and motivated to implement such practices in a range of settings.…”
Section: Introductionmentioning
confidence: 99%
“…However, Miller, Yahne, Moyers, Martinez, and Pirritano (2004), in evaluating a more in-depth training process, found significantly more change talk and less resistance in clients of MI-trained counselors and that this change was sustained at 4 months for counselors who received follow-up and coaching. More recently, Chossis et al (2007) found no difference between MI-and non-MItrained residents relating to a clients' reported number of drinks consumed and mean number of drinks per week. Yet, Brug et al (2007) found patients of MI-trained dietitians had significantly lower saturated fat intake at posttreatment.…”
Section: Training Outcomesmentioning
confidence: 94%